Synthesis, Crystal Structure, Spectral Characterization and Cytotoxic Activity of Novel Ethyl 2-Cyano-3-(quinolin-3-ylamino)acrylate - Ghorab, M.M.; Alsaid, M.S.; Ghabbour, H.A.; Fun, H.-K. (Asian Journal of Chemistry, 2014)
The chemistry of quinoline derivatives has been of increasing interest, since many of these compounds exhibited several biological activities and useful application as antitumor. On the account of the reported anticancer activity of quinolines containing the different biologically active moieties, a novel ethyl 2-cyano-3-(quinolin-3-ylamino)acrylate (2) was synthesized using 3-aminoquinoline (1) as strategic starting material. Interaction of 3-aminoquinoline (1) with ethyl 2-cyano-3-ethoxyacrylate furnished the corresponding ethyl-2-cyano-3-(quinolin-3-ylamino)acrylate (2). The structure of th newly synthesized compound was confirmed by elemental analysis, IR, 1H NMR, 13C NMR spectra and X-ray analysis. The target compound was subjected to in vitro cytotoxic activity against ehrlich ascites carcinoma cells. This compound showed higher activity with IC50 (25 μg/mL) when compared with doxorubicin [CAS 23214-92-8] as a reference drug (IC50 value 37.5 μg/mL).